2019
DOI: 10.3389/fnins.2019.00677
|View full text |Cite
|
Sign up to set email alerts
|

The 4-Aminopyridine Model of Acute Seizures in vitro Elucidates Efficacy of New Antiepileptic Drugs

Abstract: Up to date, preclinical screening for new antiepileptic substances is performed by a combination of different in vivo models of acute seizures, for which large numbers of animals are necessary. So far, little attention has been paid to in vitro models, which are also able to detect antiepileptic efficacy and in principle could likewise serve for exploratory preclinical screening. One of the established in vitro models of acute seizures is the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 85 publications
2
31
0
Order By: Relevance
“…SLE extent assessed by comparing the affected area with the total size of a given region revealed the largest expansion of epileptiform activity in the TC (68.8%) followed by the EC (68.1%). In line with the low rate of onset and propagation, expansion of SLEs within the hippocampus was low (34.0%) and involved in most of the cases the subiculum as previously reported ( Heuzeroth et al, 2019 ). All SLEs were associated with an increase in light transmittance with the maximum in the TC (ΔT/T = 2.94%) followed by the EC (ΔT/T = 2.23%) and the H (ΔT/T = 1.98%).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…SLE extent assessed by comparing the affected area with the total size of a given region revealed the largest expansion of epileptiform activity in the TC (68.8%) followed by the EC (68.1%). In line with the low rate of onset and propagation, expansion of SLEs within the hippocampus was low (34.0%) and involved in most of the cases the subiculum as previously reported ( Heuzeroth et al, 2019 ). All SLEs were associated with an increase in light transmittance with the maximum in the TC (ΔT/T = 2.94%) followed by the EC (ΔT/T = 2.23%) and the H (ΔT/T = 1.98%).…”
Section: Resultssupporting
confidence: 87%
“…Institutional security procedures were followed. Experiments were performed using combined hippocampal-entorhinal cortex (EC) slices from rats as previously reported ( Heuzeroth et al, 2019 ) with some modifications. The study design is represented in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…4-AP, a nonselective blocker of voltage-gated potassium channels, induces intense electrical discharges in brain slices 32,33 and seizure activity in experimental animals. 34 However, recently studies found that 4-AP could also be used to induce astrocytes activation directly.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of epileptiform activity in rodent brain slices can be achieved by a stand-alone manipulation such as inhibition of potassium channels by 4-aminopyridine (4-AP; Perreault and Avoli, 1991; Avoli et al, 2002; Heuzeroth et al, 2019). On the contrary, induction of epileptiform activity in human brain tissue ex vivo is less straightforward and subject to controversy.…”
Section: Methodsmentioning
confidence: 99%